Analisis Kelayakan Finansial Usahatani Kopi Liberika Di Kecamatan Tangse Kabupaten Pidie - Zakki Muhtaram; Agustina Arida; Sofyan Sofyan (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
Tangse District is one of the centers of Liberika coffee production in Pidie Regency. However, Liberika coffee production in Tangse District cannot supply market demand. Liberica coffee demand comes from the domestic market and foreign markets, for the domestic market Liberica coffee is used as a blending material and for foreign markets Liberica coffee is exported to Malaysia and also the Philippines which is the country with the highest Liberica coffee consumption. Therefore, efforts are needed to increase production by expanding land and increasing productivity. This study aims to determine the financial feasibility of Liberika coffee farming in Tangse District, Pidie Regency. The sampling technique used is themethod by stratified random samplingstratifying the sample based on the age of the coffee plant cultivated by the farmer. From a total of 665 families, the total population was taken as a sample of 10%, namely as many as 67 families. The analytical tools used are Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C), Interest Rate of Return (IRR), Payback Period (PP) and Sensitivity Analysis. The results showed that Liberika coffee farming in Pidie District, Pidie Regency was feasible when viewed from the financial aspect. This is evidenced by the NPV value 0 which is Rp. 31,787,141, -. The value of Net B/C 1 is 3.289. The value of the IRR is 41.756%, which indicates that the rate of return on capital for Liberika coffee farming is greater than the interest rate of 18%. Based on the results of sensitivity analysis using three assumptions, namely revenue decreased by 10%, operational costs increased by 10% and operational costs increased by 10% accompanied by a decrease in revenue by 100%, it was found that Liberika coffee farming in Tangse District, Pidie Regency is feasible to continue and to be developed.